Teachers in a public school engage in a study group to reach general agreements about a common approach to teaching english (2005)
This is an initial report on a study which aimed to know what happened at our school, as teachers engaged in a study group to reach general agreements about a common approach to teaching English. The first step consisted of establishing teachers’ and students’ perceptions of their needs through surveys and interviews. Discussion and analyses of the data revealed that the most focused and most favored approach by the group for teaching English is, in our specific context, the communicative approach and the development of the four basic skills using meaningful learning activities. Having agreed on this essential fact, we started the task of discussing some of the main principles of the communicative approach and what is meant by meaningful learning activities. Key words: Agreement, study group, English-teaching, pedagogical experiences, collaborative work Éste es un informe inicial de un estudio que buscó develar qué ocurrió en nuestro colegio cuando los profesores participaron en un grupo de estudio para alcanzar acuerdos generales sobre un enfoque común de enseñanza del inglés. El primer paso consistió en establecer las percepciones que los profesores y estudiantes tenían de sus propias necesidades, mediante el uso de encuestas y entrevistas. La posterior discusión y análisis de datos reveló que el enfoque más favorecido por el grupo para la enseñanza del inglés, en nuestro contexto específico, es el comunicativo y el desarrollo de las cuatro habilidades básicas utilizando actividades de aprendizaje significativas. A partir de este primer e importante acuerdo empezamos la discusión de algunos de los más importantes principios del enfoque comunicativo y lo que se entiende por actividades de aprendizaje significativas. Palabras claves: Acuerdo, grupo de estudio, enseñanza-inglés, experiencias pedagógicas, trabajo colaborativo